Diethyl 2,5-bis[(E)-2-furylmethyleneamino]thiophene-3,4-dicarboxylate - Dufresne, Stéphane (International Union of Crystallography, 2008)
The title compound, C(20)H(18)N(2)O(6)S, crystallizes as two independent molecules that are disposed about a pseudo-inversion center (1/2, 1/4, 1/8). The mean planes of the two terminal furyl rings are twisted with respect to the central thiophene ring by 7.33 (4) and 21.74 (5)° in one molecule, and by 6.91 (4) and 39.80 (6)° in the other.